Online Opportunities in Secularizing Societies? Clergy and the COVID-19 Pandemic in Ireland - Ganiel, Gladys (Religions, 2021)
This article explores how Christian clergy in Ireland have framed their adoption of online ministries during the COVID-19 pandemic as opportunities for the churches to retain some significance, even in secularizing societies. It is based on an island-wide survey of 439 faith leaders and 32 in-depth, follow-up interviews. The results of this study are analysed in light of scholarship in three areas: (1) secularization in Ireland, informed by Norris and Inglehart’s evolutionary modernization theory; (2) cross-national research that has found increasing interest in spirituality or religion during the pandemic (with the UK as the main point of comparison); and (3) wider pre-pandemic scholarship on digital religion. The article concludes by arguing that the clergy’s framing of online ministries as opportunities is important: if they regard online ministries as potential sites of religious revitalization, they are more likely to invest in them. There is some evidence that they may be assisted in this by lay volunteers. However, given the secularization already underway, it remains to be seen whether an embrace of blended online and in-person religion will have far-reaching impacts on Ireland’s religious landscape.